Semiclassical approach to the three-body muon-transfer collisions - Sultanov, R. A. [UNESP]; Sandhas, W.; Belyaev, V. B. (Springer Nature, 1999)
Muon-transfer rates in collisions of hydrogen-like atoms (pμ -) or (dμ -) with light nuclei t, 3He, 4He, 6Li or 7Li, are calculated in a semiclassical approximation to the Faddeev-Hahn equations. The two nuclei involved are treated classically, while the motion of the muon in their Coulomb field is considered from the quantum mechanical point of view. The experimentally observed strong dependence on the charge of the nuclei is reproduced.